Dendrimers and their Applications as Novel Drug Delivery Carriers - Surendra Tripathy and Malay K Das (Journal of Applied Pharmaceutical Science, 2013)
Dendrimers are novel synthetic polymeric systems having improved physical and chemical properties due to their unique three dimensional architecture. Dendrimers have a well defined size, shape, molecular weight and monodispersity. These are compatible with drug moieties as well as bioactive molecules like DNA, heparin and other polyanions. The nanoscopic size and recognition abilities make dendrimers as ideal building blocks for self-assembly and self-organization systems. The cavities inside the dendritic structure can be modified to incorporate hydrophobic and hydrophilic drugs. The terminal groups are modified to attach antibodies and bioactive substances for targeting purpose along with providing miscibility, reactivity and solubility. Currently, dendrimers are of great interest for delivering drug molecules via different routes as a nanocarrier. Toxicity problems associated with cationic dendrimers are overcome by PEGylation, which neutralizes the charge on them. Dendrimers possess suitable properties to establish itself as a potential carrier for delivery of therapeutic agents irrespective of certain synthetic and regulatory constraints. This review contains various structural aspects and properties of dendrimers along with their pharmaceutical application as a potential novel drug delivery carrier.
Keywords: Dendrimers, PAMAM, monodispersity, nanocarriers, tar